Inovasi Pelayanan Keluarga - Poerwanto, Charles; Hermanto, Yanto Paulus (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
The separation of worship between parents and children in church has a positive side, namely allowing teaching to be adjusted to the developmental level of each age. However, this separation also has an inappropriate impact, because it reduces spiritual interaction in the family and weakens the role of parents as role models of faith. The available parenting programs are generally cognitive in nature and are not accompanied by practical guidance in building the family's spiritual life. As a result, children often do not see the direct application of faith in the household, which is not in line with the principles in Deuteronomy 6:6–7. This study aims to identify challenges in family ministry and formulate integrative strategies. The methods used are literature studies and conceptual analysis of existing practices. The results of the study indicate that family-based ministry has a positive impact on children's faith growth and parental involvement. Three main strategies are proposed: Cross-Generational Worship, Family Devotion through home-based cell groups, and Applicable Spiritual Mentoring. These strategies help the church form spiritually intact families and produce generations rooted in God's word.